BiOBr-photocatalyzed cis–trans isomerization of 9-octadecenoic acids in different atmospheres. Issue 13 (5th June 2019) - Zhang, Xiaochao; Wei, Jiabing; Ren, Guangmin; Zhang, Changming; Zheng, Zhanfeng; Fan, Caimei
Abstract : Investigating systematically BiOBr photocatalyzed oleic acid isomerization in different (air, N2, and O2 ) atmospheres and the cis – trans isomerization mechanism for the first time. Abstract : This work reported for the first time a systematic investigation on a BiOBr photocatalyzed oleic acid isomerization process in different (air, N2 and O2 ) atmospheres and proposed the cis – trans isomerization mechanism to effectively restrain the formation of trans fatty acids with deleterious effects on human health. The phase structures, optical properties, and morphologies of as-prepared BiOBr were characterized by XRD, UV-vis DRS, SEM and TEM. Besides, the photocatalyzed isomerization products over BiOBr in different atmospheres were analyzed with FT-IR and 1 H NMR for comparison. The results demonstrate that there are significant differences in the photocatalytic isomerization process of oleic acid in different atmospheres, and especially the N2 atmosphere is the most favorable atmosphere, while the presence of O2 will inhibit the formation of elaidic acid. Moreover, density functional theory (DFT) was employed to calculate the charge density and energy difference of ground states between cis - and trans -isomers of oleic acid. Combining the theoretical and experimental findings, the radical cation and photo-induced h + action mechanisms in the photocatalytic isomerization process were discussed and proposed. Our findings should provide new insights and basic data for understanding the photocatalytic isomerization of unsaturated fatty acids.